Prediction of powdered activated carbon doses for 2-MIB removal in drinking water treatment using a simplified HSDM approach. (August 2016) - Yu, Jianwei; Yang, Fong-Chen; Hung, Wei-Nung; Liu, Chia-Ling; Yang, Min; Lin, Tsair-Fuh
Abstract: The addition of powdered activated carbon (PAC) is an effective measure to cope with seasonal taste and odor (T&O) problems caused by 2-methylisoborneol (2-MIB) and trans -1, 10-dimethyl- trans -9-decalol (geosmin) in drinking water. Some T&O problems are episodic in nature, and generally require rapid responses. This paper proposed a simplified approach for the application of the homogenous surface diffusion model (HSDM) to predict the appropriate PAC doses for the removal of 2-MIB. Equilibrium and kinetic experiments were performed for 2-MIB adsorption onto five PACs in three source waters. The simplified HSDM approach was compared with the experimental data, by assigning the Freundlich 1/n value in the range of 0.1–1.0 and obtaining the Freundlich equilibrium parameter K value through a 6-hr adsorption kinetic test. The model describes the kinetic adsorption data very well for all of the tested PACs in different source waters. The results were validated using the data obtained from one full scale water treatment plant, and the differences between the predicted and observed results were within 10% range. This simplified HSDM approach may be applied for the rapid determination of PAC doses for water treatment plants when faced with 2-MIB episodes in source waters. Highlights: We propose a simplified approach to quickly determine PAC dose for 2-MIB removal. After simplification, HSDM parameters were obtained by only one kinetic experiment. The Freundlich 1/n value for the approach was assumed to be in a range of 0.2–0.6. The simplified approach well predicts the data for 5 PACs in 3 source waters. The approach was further validated with the data collected from one full scale WTP.